Investigation the Effect of Spore-Forming Probiotics on the Expression of Virulence genes hly, plc, inlA of L. Monocytogenes - Sajad Rajabi; Davood Darban; Robabeh Rafie Tabatabaei; Farzaneh Hosseini (Fasa University of Medical Sciences, 2020)
Background & Objectives:  Listeria monocytogenes is known as a foodborne pathogen that causes disease in humans. Also, due to the emergence of drug resistance and the formation of biofilms in the environment, there is a need to use new methods such as probiotics to combat this bacterium. This study aimed to investigate the effect of spore-forming probiotics on hly, plc, inlA virulence genes of Listeria monocytogenes. Materials & Methods: In this study, L. monocytogenes serotype 4b strain isolated from human abortion was obtained from Microbial Bank of Iran University of Medical Sciences. Bacillus laterosporus (PTCC 1486) and Bacillus megaterium PTCC1656) were used as probiotic strains. Spore-forming probiotics were co-cultured with L. monocytogenes at different time points. The expression level of virulence genes of L. monocytogenes was assessed by real-time PCR. Results: The greatest decrease in expression under the influence of Bacillus latrosporus was related to plcA gene after 24 hours of treatment with 6 folds. Bacillus megatrium had the greatest effect on hly gene, so that at 4, 8 and 24 hours after treatment, its expression decreased by 4, 7 and 5 fold, respectively. Conclusion: The results of the present study showed that both probiotics had an inhibitory effect on the expression of Listeria monocytogenes virulence genes and the inhibitory and therapeutic properties of these probiotics should be considered.